LITERATURE REVIEW: THE RELATIONSHIP BETWEEN SMARTPHONE USE AND INCIDENTS OF ANXIETY (NOMOPHOBIA) AMONG ADOLESCENTS IN INDONESIA - Ayun Zul Silmi; Syifa’ul Lailiyah (Journal of Community Mental Health and Public Policy)
Background: Smartphones were an information and communication technology that could not be separated from human life. High-intensity use of smartphones led to addiction. Dependence on smartphones could lead to anxiety disorders or so-called nomophobia. Purpose: To determine the relationship between smartphone, use and the incidence of anxiety (nomophobia) in adolescents in Indonesia. Methods: The literature review used national articles published in 2019-2024. Articles were searched using the Preferred Reporting Items for Systematic Reviews & Meta-Analyses (PRISMA) method. Inclusion criteria include articles with quantitative research, as well as mixed methods with research subjects on adolescents in Indonesia. A total of eleven articles were included. This research used national standard articles with an article search database, namely Google Scholar and Garuda. Results: Based on the eleven articles analysed, there is a relationship between anxiety disorders (nomophobia) in adolescents in Indonesia and the intensity of their use. Conclusion: The high use of smartphones is associated with a higher tendency of nomophobia. High intensity of smartphone use is influenced by several factors, including various interesting features of smartphones, one of which is social media, the COVID-19 pandemic, and the feeling of not wanting to be left behind by trends among teenagers.